Developing An Islamic Cognitive Behavioral Therapy (I-CBT) Model to Enhance the Psychological Well-Being of Huffaz Students - Shofiah, Vivik; Rajab, Khairunnas; Syed Muhsin, Sharifah Basirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
©The authors (2025). This is an Open Access article distributed under the terms of the Creative Commons Attribution (CC BY NC) (http://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial reuse, distribution, and reproduction in any medium, provided the original work is properly cited. The study examines the relationship between Islamic Cognitive Behavioral Therapy (I-CBT), oriented practices and psychological well-being among huffaz students at Maahad Integrasi Tahfiz Istana Bandar, Selangor. Employing a mixed-methods research design, quantitative data were collected using a Psychological Well-being Scale, while qualitative insights were obtained through semi-structured interviews. The quantitative findings indicate varying levels of psychological well-being among the students: 21.13% were classified as having very high well-being, 14.08% as high, 28.17% as moderate, 19.72% as low and 16.90% as very low. Qualitative analysis, however, reveals that huffaz students generally demonstrate positive psychological attributes, particularly self-acceptance, positive interpersonal relationships, autonomy, environmental mastery, purpose in life, and personal growth. These dimensions of well-being appear to be shaped by cultural context, religiosity, social support, and personality traits embedded within the Islamic boarding school environment. The students’ engagement in the Qur’anic memorisation practices, such as talaqqi, tasmi‘ and muraja‘ah, functions as an integrated model of I-CBT by reinforcing cognitive discipline, emotional regulation, and purposeful behavior. The findings suggest that while levels of psychological well-being among huffaz students are not uniformly high, structured religious–cognitive practices within the tahfiz system contribute positively to their overall psychological development. The study highlights the potential of integrating Islamic cognitive-behavioral principles into educational and psychotherapeutic frameworks to support student well-being.